Scavenger Receptor Mediated Endocytosis of Silver Nanoparticles into J774A.1 Macrophages is Heterogeneous - Wang, Hongyun (2012)
We investigated the scavenger receptor mediated uptake and subsequent intracellular spatial distribution and clustering of 57.7 ± 6.9 nm diameter silver nanoparticles (zeta-potential = −28.4 mV) in the murine macrophage cell line J774A.1 through colorimetric imaging. The NPs exhibited an overall red-shift of the plasmon resonance wavelength in the cell ensemble as function of time and concentration, indicative of intracellular NP agglomeration. A detailed analysis of the NP clustering in individual cells revealed a strong phenotypic variability in the intracellular NP organization on the single cell level. Throughout the observation time of 24h cells containing non- or low-agglomerated NPs with a characteristic blue color coexisted with cells containing NPs with varying degrees of agglomeration, as evinced by distinct spectral shifts of their resonance wavelengths. Pharmacological inhibition studies indicated that the observed differences in intracellular NP organization resulted from coexisting actin- and clathrin-dependent endocytosis mechanisms in the macrophage population. Correlation of intracellular NP clustering with macrophage maturity marker (F4/80, CD14) expression revealed that differentiated J774A.1 cells preferentially contained compact NP agglomerates, whereas monocyte-like macrophages contained non-agglomerated NPs.